2019
DOI: 10.1136/bjophthalmol-2019-315095
|View full text |Cite
|
Sign up to set email alerts
|

Role of internal limiting membrane peeling in the prevention of epiretinal membrane formation following vitrectomy for retinal detachment: a randomised trial

Abstract: AimTo study the role of internal limiting membrane (ILM) peeling in the prevention of macular epiretinal membrane (ERM) formation following pars plana vitrectomy (PPV) for rhegmatogenous retinal detachment (RRD).MethodsIn a randomised trial, patients with macula-off RRD (duration ≤3 months) with proliferative vitreoretinopathy grade ≤C1 and absence of pre-existing maculopathy were recruited from June 2016 to May 2018. Patients were randomised into two groups: group 1 (conventional treatment) underwent PPV alon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 23 publications
4
21
0
1
Order By: Relevance
“…26 It also reduces the chances of post-operative epiretinal membrane (ERM) formation and retinal re-detachment. [27][28][29][30][31] More than 50% of eyes in our series achieved final BCVA≥20/80 while 25% of eyes achieved BCVA between 20/120-20/200. The causes for suboptimal visual gain were the development of RRD, vascular occlusion, and macular pathologies like FTMH, SRH, and macular pucker.…”
Section: Discussionmentioning
confidence: 99%
“…26 It also reduces the chances of post-operative epiretinal membrane (ERM) formation and retinal re-detachment. [27][28][29][30][31] More than 50% of eyes in our series achieved final BCVA≥20/80 while 25% of eyes achieved BCVA between 20/120-20/200. The causes for suboptimal visual gain were the development of RRD, vascular occlusion, and macular pathologies like FTMH, SRH, and macular pucker.…”
Section: Discussionmentioning
confidence: 99%
“…La incidencia de membrana epirretiniana después de una vitrectomía superó las encontradas por Takamidou et al 12 (2.4%, n = 1736) e Ishikawa et al 13 15 (74.9%, n = 64), quienes solo evaluaron con TCO y no encontraron afección visual en los pacientes. En estudios comparativos para evaluar la incidencia de membranas epirretinianas después de vitrectomía con y sin retiro de la membrana limitante interna se reportan incidencias del 20% (Kumar et al 16 , n = 30), el 31% (Forlini et al 17 , n = 81) y el 46.4% (Arias et al 18 , n = 140) en los ojos que se intervinieron sin remoción quirúrgica de la membrana limitante, lo cual es consistente con los IC95% de nuestro estudio. La remoción quirúrgica de la membrana limitante interna durante la vitrectomía casi elimina la incidencia posoperatoria de membrana epirretiniana, pero puede llevar a una menor recuperación visual y a otras alteraciones funcionales clínicas o subclínicas 11,19 .…”
Section: Discussionunclassified
“…In addition to the demonstrated advantage of macular ILM peeling on rates of surgical success, we found that postoperative ERM formation was significantly reduced when macular ILM peeling was performed compared with not (7.4% vs. 18.8%; P = 0.01) (Table 4), in keeping with a recent study. 19 Furthermore, macular ILM peeling may be of particular benefit in phacovitrectomy where combined surgery has been shown to lead to more intense postoperative inflammation 7 with a presumably higher risk of postoperative ERM development.…”
Section: Discussionmentioning
confidence: 99%